A model for capturing the software architecture design process of mobile systems - Roldán, María Luciana (2010)
Numerous efforts have addressed the problem of defining the fundamental architectural building blocks and methods for modelling software architectures in dynamic mobile environments. However, there is a lack of tools for documenting the evolution of the products generated during the design of software architectures for mobile systems. Based on a generic versioning administration scheme, a model to capture and manage the products of a software architecture design process is proposed placing the focus on mobility concerns. This model follows an operational approach, where design decisions are represented as architectural operations that are captured when they are applied during a design project. The capture of this information enables the tracing of such a design process and its resulting products.